2002
DOI: 10.1557/proc-716-b13.3
|View full text |Cite
|
Sign up to set email alerts
|

Length Effects on the Reliability of Dual-Damascene Cu Interconnects

Abstract: Abstract--The effects of interconnect length on the reliability of dual-damascene Cu metallization have been investigated. As in Al-based interconnects, the lifetimes of Cu lines increase with decreasing length. However, unlike Al-based interconnects, no critical length exists, below which all Cu lines are 'immortal'. Furthermore, we found multi-modal failure statistics for long lines, suggesting multiple failure mechanisms. Some long Cu interconnect segments have very large lifetimes, whereas in Al segments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Dominant role of Cu/dielectric cap interface in electromigration is reported [1,10,59,61,62,66,68,123] and was also observed in our electromigration characterizations. If this interface is modified so as to make it more resistant to electromigration, the dominant path for electromigration can be retarded leading to better reliability.…”
Section: Surface Treatmentssupporting
confidence: 85%
See 2 more Smart Citations
“…Dominant role of Cu/dielectric cap interface in electromigration is reported [1,10,59,61,62,66,68,123] and was also observed in our electromigration characterizations. If this interface is modified so as to make it more resistant to electromigration, the dominant path for electromigration can be retarded leading to better reliability.…”
Section: Surface Treatmentssupporting
confidence: 85%
“…Others have indicated that the Cu/liner interface is the fast electromigration path [94]. interesting to note that in some reports [66,68,123,140] voids were observed to be at Cu/Si3N 4 interface away from the via for some of the samples (Figure 5.1), but these were ignored and not enough explanation is provided. Actually these voids must be the voids that were nucleated at the Cu/Si3N 4 interface away from the via and moving towards the cathode end, according to the proposed mechanism in this thesis.…”
Section: Electromigration Mechanism In Standard Dual-damascene Structmentioning
confidence: 97%
See 1 more Smart Citation
“…Findings from the in situ electromigration studies 2,3 and the model proposed herein warrant reinvestigation of electromigration mechanisms. Mechanisms responsible for the well-known reservoir effect 15,16 and short-length effect [17][18][19] are speculated based on the proposed model. The reservoir effect is generally understood based on the theory of maximum tensile stress developed at the cathode flux divergence site (cathode via bottom liner).…”
Section: Resultsmentioning
confidence: 99%
“…This asymmetry in the void volume required for failure not only accounts for the M1-M2 asymmetry in lifetimes but also contributes to the different short length effects for immortality in via-above (M1) and via-below (M2) type of interconnects. At short lengths, the reliability improves for both Al and Cu interconnects [3,[6][7][8][9]. However, unlike Al interconnects, the tolerable non-fatal void volumes in M1 and M2 structures are different.…”
Section: Contrasting Failure Characteristicsmentioning
confidence: 99%